Evidence of bottleneck effect on hepatitis C virus transmission between a couple under interferon based therapy - da Silva, Rafael Alves; de Carvalho, Isabel Maria Vicente Guedes; de Matos, Renata Prandini Adum [UNESP]; Yamasaki, Lilian Hiromi Tomonari [UNESP]; Bittar, Cíntia [UNESP]; Rahal, Paula [UNESP]; Jardim, Ana Carolina Gomes [UNESP] (Elsevier, 2017)
Issues on the correlation of viral genetic diversity and treatment response to the hepatitis C infection remain uncertain. The bottleneck effect dictates the characteristics of the viral population that will establish the infection in a new host and is related to how the immune system and treatment will be effective against the virus. Here we evaluated the phylogenetic characteristics of quasispecies population and the treatment response pattern of a HCV infected couple. We also analyzed whether the viral population of these patients indicated that they were exposed to the same source for primer infection. This study included two patients (P10 and P11) HCV genotype 1b infected. The couple presented horizontal transmission. Viral RNA was isolated from serum samples collected before, during and after treatment, at specific time points. The HCV NS5A gene sequence was amplified, cloned and sequenced. Genetic and evolutionary analyses were performed to compare the quasispecies population of these two patients and local control patients. Genetic distance and diversity were calculated. Phylogenetic analyses were performed by using maximum likelihood and Bayesian methodologies. The analysis of the baseline samples showed that the genetic distance of the viral populations of patients P10 and P11 was significantly lower than when these patients and the control group based on sequences from local patients were analyzed, supporting the horizontal transmission hypothesis. Phylogenetic analysis with sequences from all the time point samples also demonstrated two patterns of evolution depending on the treatment response. The Bayesian analysis showed that one isolate corresponding to the baseline sample of P10 was grouped into the P11 clade, suggesting a way of infection and a bottleneck effect. Our data suggests that the patient P11 viral population may be originated from variants from P10 patient and consequently showing that clinical differences between treatment responses can emerge from the bottleneck effect on viral populations.
Keywords: Bottleneck; Hepatitis C; Phylogenies; Viral evolution; Viral transmission